2006
DOI: 10.1200/jco.2006.07.7016
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Pemetrexed Combined With Either Cisplatin or Carboplatin in Untreated Extensive-Stage Small-Cell Lung Cancer

Abstract: Pemetrexed/platinum doublets had activity and appeared to be well-tolerated in first-line ES-SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 34 publications
2
56
1
1
Order By: Relevance
“…Over recent decades, numerous biological targets such as targeted agents and new cytotoxic drugs for NSCLC have been identified for anticancer therapies and significant progress has been made in the treatment of malignancies (Sandler et al 2006;Socinski et al 2006;Mok et al 2009). However, little progress has been made in the treatment of SCLC and no targeted agents have prolonged the OS for SCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent decades, numerous biological targets such as targeted agents and new cytotoxic drugs for NSCLC have been identified for anticancer therapies and significant progress has been made in the treatment of malignancies (Sandler et al 2006;Socinski et al 2006;Mok et al 2009). However, little progress has been made in the treatment of SCLC and no targeted agents have prolonged the OS for SCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data from phase I and II trials suggested antitumoural activity and toxicity comparable to standard treatment regimens with EP or cisplatin/irinotecan [25].…”
Section: Alternatives To Platin/etoposidementioning
confidence: 97%
“…SCLC is an extremely aggressive malignancy, with significantly shortened doubling time, higher growth fraction, and earlier onset of remote metastasis, is usually sensitive to chemotherapy with an objective response rate of 80-90% (Schiller et al, 2001;Simon et al, 2003;Stupp et al, 2004;Socinski et al, 2006;Jemal et al, 2010). There is an intersection between SCLC and NSCLC that the WHO/IASLC classification in 1999 defined combined small cell lung carcinomas (C-SCLC).…”
Section: Introductionmentioning
confidence: 99%